Enhanced rice (Oryza sativa L.) plant growth and nutrient contents during the vegetative stage through zinc solubilizing bacterial bead inoculation - Irsyad Sulaimi Ramly; Nur Maizatul Idayu Othman; Aida Soraya Shamsuddin; Tan, Ali Kee Zuan; Nor Hafizah Zakaria; Fadzilah Adibah Abdul Majid; Nur’ Amira Hamid (Penerbit Universiti Kebangsaan Malaysia, 2024)
Zinc-solubilizing bacteria (ZSB) can increase zinc bioavailability in soil and transform insoluble zinc into an accessible form, which helps reduce crop zinc deficiencies, simultaneously improving soil fertility and crop nutrition. The effects of two ZSB strains, Acinetobacter nosocomialis (SR R-10) and Acinetobacter seifertii (SR-12) were evaluated in the present study on the rice plant growth and nutrient contents using the bead inoculation method. A completely randomized design (CRD) was employed and four treatments were applied: 1) non-inoculated (control), 2) SR R-10 strain, 3) SR R-12 strain, and 4) mixed inoculation of SR R-10 and SR R-12 strains. After 40 days of sowing, the growth parameters were measured. The results revealed that SR R-10 inoculant enhanced the growth by producing the tallest plant (63.47 ± 1.87 cm) and longest root (19.93 ± 0.48 cm). SR R-10-treated plants also showed the highest leaf count (32 ± 0.58 leaves) and Soil Plant Analysis Development (SPAD) value (32.67 ± 1.59). The mixed inoculant showed synergistic benefits, indicated by the higher plant height, SPAD reading, and leaf count, compared to the non-inoculated treatment. SR R-10 and mixed inoculant increased plant biomass, measuring 4.67 ± 0.30 g and 4.40 ± 0.28 g, respectively, compared to non-inoculated plants (3.19 ± 0.17 g). For nutrient content, plants with SR R-10 inoculation showed the highest concentration of nitrogen (2.24 ± 0.00%), phosphorus (0.24 ± 0.00%), potassium (2.79 ± 0.03%), and zinc (59.51 ± 2.69 mg kg-1). Mixed inoculant also improved soil fertility by increasing the available Zn (6.17 mg kg-1) in the soil, however, it lowered the soil pH to pH 5.8. These findings highlight the potential of ZSB, particularly A. nosocomialis (SR R-10), to improve rice plant’s growth and nutritional quality and increase the bioavailability of zinc in the soil to promote sustainable agricultural practices.